A Study on Pollen Viability of Piper colubrinum Link - Shang, Chen Yi; Cheksum Supiah, Tawan; Paulus Amin, Det; Liang, Sim Soon (Journal of Agricultural Science and Technology B 2, 2012)
Pollen viability study on Piper colubrinum Link. carried out to develop interspecific hybridization between P. nigrum L. and P. colubrinum Link.. This plant has good potential as a donor plant in breeding programme for Phytophthora to foot rot resistance in the cultivated species, P. nigrum. This project was carried out to reveal the optimum time to collect pollen of P. colubrinum for artificial pollination. Through this study, anther dehiscence was proved occurred around 9 am. Based on the result obtained from study on the time of anther dehiscence, the pollen was classified into five stages for testing on the viability, i.e., stage 1, before anther dehiscence, i.e., around 7 am (pollen obtained by crushing on the anther); stage 2: immediately after anther dehiscence, i.e., around 9 am; stage 3: two hours after anther dehiscence, i.e., around 11 am; stage 4: four hours after anther dehiscence, i.e., around 1 pm; and stage 5: six hours after anther dehiscence, i.e., around 3 pm. Data obtained from pollen germination and pollen tube growth study showed that pollen of P. colubrinum was the most viable at two hours after anther dehiscence and onward. It was also proved that the viability can be maintained up to at least eight hours. Pollen obtained before anther dehiscence by crushing on the anther was found less viable with lower percentage of pollen germination and retarded pollen tube growth. In other words, the experiment enlightened that artificial pollination between P. nigrum L. and P. colubrinum Link was ideally to be carried out approximately starting from 11 am until 5 pm, considering the viability of pollen of P. colubrinum.